Therapeutic arteriogenesis by factor-decorated fibrin matrices promotes wound healing in diabetic mice. (September 2022) - D'Amico, Rosalinda; Malucelli, Camilla; Uccelli, Andrea; Grosso, Andrea; Di Maggio, Nunzia; Briquez, Priscilla S; Hubbell, Jeffrey A; Wolff, Thomas; Gürke, Lorenz; Mujagic, Edin; Gianni-Barrera, Roberto; Banfi, Andrea
Chronic wounds in type-2 diabetic patients present areas of severe local skin ischemia despite mostly normal blood flow in deeper large arteries. Therefore, restoration of blood perfusion requires the opening of arterial connections from the deep vessels to the superficial skin layer, that is, arteriogenesis. Arteriogenesis is regulated differently from microvascular angiogenesis and is optimally stimulated by high doses of Vascular Endothelial Growth Factor-A (VEGF) together with Platelet-Derived Growth Factor-BB (PDGF-BB). Here we found that fibrin hydrogels decorated with engineered versions of VEGF and PDGF-BB proteins, to ensure protection from degradation and controlled delivery, efficiently accelerated wound closure in diabetic and obese db/db mice, promoting robust microvascular growth and a marked increase in feeding arterioles. Notably, targeting the arteriogenic factors to the intact arterio-venous networks in the dermis around the wound was more effective than the routine treatment of the inflamed wound bed. This approach is readily translatable to a clinical setting.